2001
DOI: 10.1007/s001270170036
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the relation between parental education as well as occupation and problem behaviour in Dutch 5- to 6-year-old children

Abstract: Parental education and occupation have a large impact on the mental health of young children. Psychosocial and biological factors are possible explanations for this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 26 publications
5
57
2
2
Order By: Relevance
“…26,27 Low socioeconomic status (low education of the parents) and maternal smoking have consistently been shown to increase the risk for psychosocial problems, especially for behavioral problems. [28][29][30][31] Our findings show that PCH professionals do indeed identify and register the predictive factors that are found in these previous studies.…”
Section: Discussionsupporting
confidence: 53%
“…26,27 Low socioeconomic status (low education of the parents) and maternal smoking have consistently been shown to increase the risk for psychosocial problems, especially for behavioral problems. [28][29][30][31] Our findings show that PCH professionals do indeed identify and register the predictive factors that are found in these previous studies.…”
Section: Discussionsupporting
confidence: 53%
“…Concerning the child-related factors, Velez et al (1989) reported that stressful life events are important risk factors for both internalizing and externalizing disorders. Low-level parental occupation (Campbell, 1995;Kalff et al, 2001a), family size (Williams et al, 1990), race (Costello et al, 1996), family structure (Velez et al, 1989), low maternal age at delivery (Orlebeke et al, 1998), and maternal depression (Lavigne et al, 1998) are important family-related risk factors. Although the environment in which a child grows up is a potential risk factor for behavioral problems (Kalff et al, 2001b), little is known about its influence on DSM-based diagnoses (Hermanns and Leu, 1998).…”
Section: A Longitudinal Community Study: Do Psychosocial Riskmentioning
confidence: 99%
“…Although the environment in which a child grows up is a potential risk factor for behavioral problems (Kalff et al, 2001b), little is known about its influence on DSM-based diagnoses (Hermanns and Leu, 1998). Data were collected during a longitudinal population study in the south of the Netherlands, titled the Study of Attention Disorders in Maastricht (SAM), that used a two-stage design (Kalff et al, 2001a;Kroes et al, 2001). In the first stage, the children were screened with the Child Behavior Checklist (CBCL) (Verhulst et al, 1996) and psychosocial risk factors were obtained.…”
Section: A Longitudinal Community Study: Do Psychosocial Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns estudos demonstram que possa haver marcadores fenotípicos familiares [63][64][65] , bem como marcadores genéticos 66,67 .…”
Section: Prognósticounclassified